Health professional-patient communication practices in East Asia: An integrative review of an emerging field of research and practice in Hong Kong, South Korea, Japan, Taiwan, and Mainland China. Issue 7 (July 2018) - Pun, Jack K.H.; Chan, E. Angela; Wang, Sophie; Slade, Diana
Highlights: It is problematic to interpret Asian practices through the lens of Western models. This review offers an in-depth view of health communication in East Asian context. It summarises evidences on cultural practices of health communication in Asia. This paper urges for developing culturally-specific models of health communication. Clinicians should build on Asian specifics to improve relationship with patients. Abstract: Objective: To provide an integrative review of literature on health communication in East Asia and detail culturally-specific influences. Methods: Using PRISMA model, search of PubMed, PsychInfo, Web of Knowledge, ERIC and CINAHL databases were conducted for studies between January 2000 and March 2017, using the terms 'clinician/health professional-patient', 'nurse/doctor-patient, 'communication' and 'Asia'. Results: 38 studies were included: Mainland China, Hong Kong, Japan, South Korea, and Taiwan. The existing body of research on clinician patient communication in East Asia can be classified: 1) understanding the roles and expectations of the nurse, clinician, patient, and family in clinician-patient consultations: a) nurse-patient communication; b) doctor-patient communication; c) the role of family member; and 2) factors affecting quality of care: d) cultural attitudes towards death and terminal illnesses; e) communication preferences affecting trust, decision-making and patient satisfaction; f) the extent to which patient centred care is being implemented in practice; and g) communication practices in multilingual/multi-disciplinary environments. Conclusion: The review detailed the complexity and heterogeneity of clinician-patient communication across East Asia. The studies reviewed indicate that research in East Asia is starting to move beyond a preference for Western-based communication practices. Practice implications: There is a need to consider local culture in understanding and interpreting medical encounters in East Asia. The paper highlights the need for a specific culturally-appropriate model of health communication in East Asia which may significantly improve relationships between clinicians and patients.